Comparative analysis of CB-PWM techniques in modified multilevel DC link inverter for PV applications - Pilli N.K.; Singh S.K. (My University, 2025)
The performance analysis of modified multilevel DC link inverter (MMLDCLI) operating with various carrier-based pulse width modulation (CB-PWM) techniques is studied. In MMLDCLI, seven-level is achieved with six controllable switches only, making it an attractive option as a reduced device count multilevel (MLI, multilevel inverter) topology. MMLDCLI operates with two different levels of voltage source, and the absence of transformer makes this topology suitable for photovoltaic (PV) applications. Two different levels of sources can be achieved with two different combinations of PV panel arrangements. The CB-PWM is reputed modulation approach for MLIs. In this study, various CB-PWM techniques are implemented for MMLDCLI to evaluate performance parameters such as harmonic analysis, device losses and device stress. All the simulations are performed in SIMULINK, and hardware prototype is developed to validate the results. © The Institution of Engineering and Technology 2019.